Study of glucose specimen integrity in various blood collection tubes over a period of 24 hours - Warade, Jayesh Prabhakar (International Journal of Research in Medical Sciences, 2024)
Background: Blood glucose testing is performed to diagnose and monitor conditions such as diabetes mellitus and gestational diabetes in pregnant women. Accurate measurement of plasma glucose concentration is an important component. Here, we have compared the glucose estimation in specimen collected in various collection tubes. Methods: The samples were stored at 2-4°C temperature and at 0, 4, 12 and 24 hrs aliquots were taken and were processed. Plasma glucose was determined using the glucose oxidase enzymatic methods on the Beckman coulter AU700. All the results at 0 hour were compared with results at 4 hours, 12 hours and 24 hours. Also results of fluoride tubes were compared with results of EDTA, heparin and plane tubes. Results: We have found no significant difference between results of glucose estimation obtained using samples collected in serum tubes, EDTA tubes, fluoride tube and lithium heparin tube even after 24 hours after separation of serum/plasma. Conclusions: From this study we have concluded that blood samples collected in plane serum tube, fluoride tubes, EDTA tubes and heparin tubes produce similar results for estimation of glucose if the collected samples are centrifuged immediately after collection for separation of plasma and serum.